Measurement of Quality of Life VI. Quality-Adjusted Life Years (QALY) is an Unfortunate Use of the Quality-of-Life Concept - Soren Ventegodt; Joav Merrick; Niels Jorgen Andersen (The Scientific World Journal)
The QALY (quality-adjusted life years) attempts to incorporate the dimension of quality of life into the evaluation by adjusting life years by a quality factor. In practice, this is based on discussing with people the progression of a number of hypothetical illnesses and their ensuing side effects. From this information, the person assesses how each state of health described compares with a theoretical maximum state of health. For example, 1 day with a certain condition might the equivalent of living only 0.5 days in good health.We believe that QALY value only represents a superficial impression of a person's quality of life. In short, the QALY does not express what it means for a person to live a life at reduced quality. We believe that if the patients were optimally informed and allowed to decide for themselves, they would more often reject high-tech expensive biomedical treatments that only serve to prolong life and do not increase its quality. The problem of priorities may then turn out to be far more simple and also more ethical: the focus will be on the quality of life, not on QALY, and the question of the meaning of life and death will achieve greater openness and respect.